A Novel Matrix Metalloprotease-like Enzyme (Karilysin) of the Periodontal Pathogen Tannerella forsythia ATCC 43037 - Karim, Abdulkarim Y. (2010)
Proteases of Tannerella forsythia, a pathogen associated with periodontal disease, are implicated as virulence factors. Here, we characterized a matrix metalloprotease (MMP)-like enzyme of T. forsythia referred to as karilysin. Full length (without a signal peptide) recombinant karilysin (49.9 kDa) processed itself into the mature 18 kDa enzyme through a sequential autoproteolytic cleavages both at N- and C-terminal profragments. The first cleavage at the Asn14-Tyr15 peptide bond generated the fully active enzyme (47.9 kDa) and subsequent truncations at the C-termini did not affect proteolytic activity. Mutation of Tyr15 to Ala generated a prokarilysin variant that processed itself into the final 18 kDa form with greatly reduced kinetics. Inactive prokarilysin with the mutated catalytic Glu residue (E136A) was processed by active karilysin at the same sites as the active enzymes. The karilysin proteolytic activity and autoprocessing were inhibited by 1,10-phenanthroline and EDTA. Calcium ions were found to be important for both activity and thermal stability of karilysin. Using the CLiPS technology, specificity of karilysin was found to be similar to that of MMPs with preference for Leu/Tyr/Met at P1′ and Pro/Ala at P3. This specificity and the ability to degrade elastin, fibrinogen and fibronectin may contribute to the pathogenicity of periodontitis.